Effect of Phyllanthus amarus in sodium arsenite-induced tissue damage - Hashim Achummantakath; Krishnan Subhadra Prasanna; A. S. Nizamudeen (Bangladesh Pharmacological Society, 2022)
This study aims to evaluate the effect of alcoholic extract of Phyllanthus amarus leaves on arsenic-induced histological changes in Wistar rats. Rats were divided into 4 groups: Group I: normal control; Group II: rats received sodium arsenite (40 mg/kg); Group III: rats received sodium arsenite (40 mg/kg) + P. amarus extract (100 mg/kg); Group IV: rats received sodium arsenite (40 mg/kg) + extract (200 mg/kg). All groups were treated by oral gavage with sodium arsenite for 28 days and the animals were subsequently administered (oral) with 100 and 200 mg/kg extract, once daily for two weeks. Animals were sacrificed 24 hours after the last treatment and different organs were collected for histopathological analysis. Results revealed mild to severe type of necrosis and degenerative changes in brain, kidney, and liver of arsenic fed animals. In rats administered with extract showed significant improvements, and the normal histological feature of the cells was almost restored in rats.  These suggest that P. amarus can be used to treat arsenic-induced multi-organ damages.